Effects of Fasudil on Patients with Pulmonary Hypertension Associated with Left Ventricular Heart Failure with Preserved Ejection Fraction: A Prospective Intervention Study - Xiang Zhang; Xueming Zhang; Saihua Wang; Jun Luo; Zhihong Zhao; Changzhu Zheng; Jieyan Shen (Canadian Respiratory Journal)
Background. Pulmonary hypertension due to left ventricular heart failure with preserved ejection fraction (PH-HFpEF) is an increasingly medical problem. The aim of the study was to evaluate the clinical efficacy of fasudil on PH-HFpEF elderly patients and to figure out the subtype of PH-HFpEF which may be the therapeutic object of fasudil. Method. 58 PH-HFpEF elderly patients were enrolled. Patients were diagnosed with passive pulmonary hypertension (PPH) or reactive pulmonary hypertension (RPH) by right heart catheterization and all receiving Rho kinase inhibitor fasudil for 2 weeks. The endpoint includes changes in SpO2, NT-pro BNP, cardiac functional classification, and echocardiography measurements after 2 weeks treatment. Results. The course of disease in the RPH group was longer than the PPH group (p<0.05). Cardiac output was found to be worse in the RPH group than the PPH group (p<0.01). Besides, the RPH group demonstrated a greater transpulmonary pressure gradient (TPG) and pulmonary vascular resistance (PVR) than the PPH group (p<0.01 for both) as well as pulmonary arterial systolic pressure (PASP) and mean pulmonary arterial pressure (mPAP) (p<0.01 for both), which fits the feature of RPH. After treatment of fasudil, in RPH group, PASP significantly decreased (p<0.01) with decreased E/E′ and increased E/A (p<0.05 for both), indicating that pulmonary haemodynamics and cardiac diastolic function were ameliorated, but the measurements in the PPH group had no significant changes. NT-pro BNP and 6 MWD of both groups were improved (p<0.05). The total effective rate of the RPH group was 74.29%, which was higher than 47.83% of the PPH group (p<0.05). Conclusion. The Rho kinase inhibitor fasudil can improve pulmonary and left ventricular haemodynamics in patients with PH-HFpEF. The total effective rate was higher in the RPH group. Fasudil may be a promising targeted drug for the RPH in PH-HFpEF patients. This trial is registered with ChiCTR-INR-16009511.